Germination and Regeneration of Cymbidium findlaysonianum Lindl. on a Medium Supplemented with Some Organic Sources - TAWARO, Supavadee; SURANINPONG, Potjamarn; CHANPRAME, Sontichai (Walailak Journal of Science and Technology (WJST), 2011)
Seeds of Cymbidium findlaysonianum Lindl. were germinated and regenerated on media supplemented with various additives. After germination for 3 months, solidified Vacin and Went (VW) medium supplemented with, 15 % coconut water, 5 % banana homogenate, 5 % potato homogenate, 0.2 % activated charcoal and 20 g/l sucrose promoted higher seedling germination than the control medium. The number of protocorm cultured in a modified liquid VW medium with Murashige and Skoog (MS) vitamin (VWM) increased 4 times for every month of culture, a significant difference from the VW medium, MS medium and half strength MS medium (½ MS). Moreover, the activated charcoal added to the medium stimulated seedlings growth significantly more than when coconut water, banana homogenate and/or potato homogenate were added to the medium. Healthy plants transferred to a plastic tray containing coconut peat successfully acclimatized (70 %) in the greenhouse. More than 100,000 plantlets may be obtained from a capsule after being cultured for a year. Thus, organic additives and medium components had an effect on the growth and development of asymbiotic seeds in C. findlaysonianum.